AN ANALYSIS OF INDONESIAâ€™S EXPORT VALUE TO ASEAN COUNTRIES BEFORE AND AFTER ASEAN ECONOMIC COMMUNITY (AEC) - Tumober, Jennifer Roselyn; Pangemanan, Sifrid S.; Rumokoy, Farlane S (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Counting back since the formation of Association of Southeast Asian Nations (ASEAN), it took Indonesia and the other members of ASEAN 48 years to arrive at ASEAN Economic Community (AEC) establishment. This research aims to evaluate the export value performance as one of the things countries seek and expect when conducting or joining an economic integration. The study examines the change in the export value of Indonesia to the other nine members of ASEAN 1 year before and 1 year after the establishment of AEC using Wilcoxon signed rank test. The result shows a significant positive change in Indonesiaâ€™s export value to ASEAN countries before and after AEC with 90% year-on-year growth. Thailand dominates the value contribution to the total export value with 84% contribution leaving only 16% contribution for the rest of ASEAN members (Singapore 5%, Malaysia 2%, Philippines 2%, Vietnam 2%, Myanmar 2%, while Cambodia, Brunei Darussalam, and Lao PDR contribute 0%). Furthermore, mineral fuels, mineral oils and products of their distillation and bituminous substances are the top commodity of Indonesia to ASEAN countries after AEC delivering 22% contribution to the total export value. AEC giving Indonesia an easier access to 9 member countries of ASEAN. Indonesiaâ€™s export that only focus to Thailand is a quiet risky step as one of the famous investment theory stated â€œdonâ€™t put your eggs in the same basketâ€. Lastly, the domestic value-adding industry needs special attention from government because of the high raw materials export commodity that still high.Keywords: asean economic community (aec), economic integration, export, wilcoxon signed rank test